Pengaruh Kinerja Housekeeping Attendant terhadap Kepuasan Tamu di Swiss-Belinn Manyar SURABAYA - Achmad Maulana; Diah Renata Anggraeni (Yayasan Literasi Sains Indonesia, 2025)
The Influence of Housekeeping Performance on Guest Satisfaction in the Housekeeping Department at Swiss-Belinn Manyar Surabaya. Supervised and supervised by Ibu. Diah Renata Anggraeni S.Tr. Par., M.M. The hotel industry is a service sector that relies heavily on service quality to create guest satisfaction. In hotel operations, the Housekeeping Department plays a crucial role in maintaining the cleanliness, comfort, and completeness of guest rooms. One key element in this department is the Swiss-Belinn Manyar Surabaya Housekeeping Attendant, who is directly responsible for maintaining and preparing rooms to ensure they are habiTabel according to hotel standards. This study aims to investigate the influence of housekeeping attendant performance on guest satisfaction in the Housekeeping Department at Swiss-BelInn Manyar Surabaya. Because this study aims to measure the influence between variables (X on Y), a quantitative approach is most appropriate. Data were collected through questionnaires and analyzed statistically using linear regression or correlation. The data analysis used in this study consisted of simple linear regression analysis using SPSS and Microsoft Excel with 100 respondents. The results of this study conclude that housekeeping attendant performance influences guest loyalty. This is evidenced by the significance probability score of Sig. = 0.000. The results show that the significance is less than 0.05 (Sig. <0.05), while the coefficient of influence of variable X on variable Y is 0.985, indicating a fairly strong relationship between housekeeping attendant performance and guest satisfaction in the housekeeping department, as the R value is less than 1.